The Contribution of Universities to Growth: Empirical Evidence for Italy - Martin Carree; Antonio Della Malva; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
New entrepreneurial ventures may represent a viable and effective mechanism to transform academic knowledge into regional economic growth. We test this notion for the Italian provinces between 2001 and 2006. We evaluate three outputs of academic activities: teaching, research and Intellectual Property Rights (IPR) activities management. New ventures may be able to transform the mentioned outputs into improved economic performance. The findings show that the effects of academic outputs on provincial economic growth (all sectors) are appreciable when they are associated with sustained entrepreneurial activities in the province. It suggests that academic inquiry may provide new ventures with valuable commercial opportunities overseen by established companies.
Keywords: I23; O18; O34; R11; 330